Facial expression recognition in Alzheimer’s disease: a longitudinal study - Bianca Torres; Raquel Luiza Santos; Maria Fernanda Barroso de Sousa; José Pedro Simões Neto; Marcela Moreira Lima Nogueira; Tatiana T. Belfort; Rachel Dias; Marcia Cristina Nascimento Dourado (Arquivos de Neuro-Psiquiatria)
Facial recognition is one of the most important aspects of social cognition. In this study, we investigate the patterns of change and the factors involved in the ability to recognize emotion in mild Alzheimer’s disease (AD). Through a longitudinal design, we assessed 30 people with AD. We used an experimental task that includes matching expressions with picture stimuli, labelling emotions and emotionally recognizing a stimulus situation. We observed a significant difference in the situational recognition task (p ≤ 0.05) between baseline and the second evaluation. The linear regression showed that cognition is a predictor of emotion recognition impairment (p ≤ 0.05). The ability to perceive emotions from facial expressions was impaired, particularly when the emotions presented were relatively subtle. Cognition is recruited to comprehend emotional situations in cases of mild dementia.